Examples of Integration of Cryopreservation in different Plant Biotechnology Programmes - Florin, Bruno; Brulard, B (MTT, 2008)
Cryopreservation appears as an alternative to the preservation of biodiversity due to the risks to lose a part of the genetic resources by climatic disaster, human activities, pests and diseases. Genetic resources are a prerequisite for the establishment of classical and modern plant breeding programmes. By integrating cryopreservation in different biotechnology programmes, the breeders contribute to the preservation of genetic resources and ensure the chance to maintain the plant improvement process. The first step is the creation of a core collection representative of the genetic diversity and including wild and improved varieties. Considering recalcitrant species like coffee and cacao, the development of cryopreservation permitted to secure the core collection. But another advantage is the possibility to maintain embryogenic potential of strains established for elite clones for further propagation. On another hand, to maintain by in vitro culture chicory selected parental clones for seed production or tissues culture stock established for various research purposes is time consuming and exposed to the various risks like contaminations, loss of strain or somaclonal variation. Cryopreservation has been used as a solution to preserve various plant materials for new potential research programme and to reduce efforts to subculture collection. Cryopreservation is now routinely used at the R&D Centre on various species comprising a large number of coffee, cacao and chicory varieties as well as on a collection of tissue cultures established for pharmaceutical, cosmetic purpose of more 100 plant species.
Keywords: Ka; biodiversity; genetic resources; plant breeding; core collection; coffee; cacao; chicory